src/HOL/Extraction/Pigeonhole.thy
 author berghofe Sat, 06 Aug 2005 18:06:56 +0200 changeset 17027 8bbe57116d13 parent 17024 ae4a8446df16 child 17145 e623e57b0f44 permissions -rw-r--r--
Tuned comment.
```
(*  Title:      HOL/Extraction/Pigeonhole.thy
ID:         \$Id\$
Author:     Stefan Berghofer, TU Muenchen
*)

header {* The pigeonhole principle *}

theory Pigeonhole imports EfficientNat begin

text {*
We formalize two proofs of the pigeonhole principle, which lead
to extracted programs of quite different complexity. The original
formalization of these proofs in {\sc Nuprl} is due to
Aleksey Nogin \cite{Nogin-ENTCS-2000}.

We need decidability of equality on natural numbers:
*}

lemma nat_eq_dec: "\<And>n::nat. m = n \<or> m \<noteq> n"
apply (induct m)
apply (case_tac n)
apply (case_tac  n)
apply (simp only: nat.simps, rules?)+
done

text {*
We can decide whether an array @{term "f"} of length @{term "l"}
contains an element @{term "x"}.
*}

lemma search: "(\<exists>j<(l::nat). (x::nat) = f j) \<or> \<not> (\<exists>j<l. x = f j)"
proof (induct l)
case 0
have "\<not> (\<exists>j<0. x = f j)"
proof
assume "\<exists>j<0. x = f j"
then obtain j where j: "j < (0::nat)" by rules
thus "False" by simp
qed
thus ?case ..
next
case (Suc l)
thus ?case
proof
assume "\<exists>j<l. x = f j"
then obtain j where j: "j < l"
and eq: "x = f j" by rules
from j have "j < Suc l" by simp
with eq show ?case by rules
next
assume nex: "\<not> (\<exists>j<l. x = f j)"
from nat_eq_dec show ?case
proof
assume eq: "x = f l"
have "l < Suc l" by simp
with eq show ?case by rules
next
assume neq: "x \<noteq> f l"
have "\<not> (\<exists>j<Suc l. x = f j)"
proof
assume "\<exists>j<Suc l. x = f j"
then obtain j where j: "j < Suc l"
and eq: "x = f j" by rules
show False
proof cases
assume "j = l"
with eq have "x = f l" by simp
with neq show False ..
next
assume "j \<noteq> l"
with j have "j < l" by simp
with nex and eq show False by rules
qed
qed
thus ?case ..
qed
qed
qed

text {*
This proof yields a polynomial program.
*}

theorem pigeonhole:
"\<And>f. (\<And>i. i \<le> Suc n \<Longrightarrow> f i \<le> n) \<Longrightarrow> \<exists>i j. i \<le> Suc n \<and> j < i \<and> f i = f j"
proof (induct n)
case 0
hence "Suc 0 \<le> Suc 0 \<and> 0 < Suc 0 \<and> f (Suc 0) = f 0" by simp
thus ?case by rules
next
case (Suc n)
{
fix k
have
"k \<le> Suc (Suc n) \<Longrightarrow>
(\<And>i j. Suc k \<le> i \<Longrightarrow> i \<le> Suc (Suc n) \<Longrightarrow> j < i \<Longrightarrow> f i \<noteq> f j) \<Longrightarrow>
(\<exists>i j. i \<le> k \<and> j < i \<and> f i = f j)"
proof (induct k)
case 0
let ?f = "\<lambda>i. if f i = Suc n then f (Suc (Suc n)) else f i"
have "\<not> (\<exists>i j. i \<le> Suc n \<and> j < i \<and> ?f i = ?f j)"
proof
assume "\<exists>i j. i \<le> Suc n \<and> j < i \<and> ?f i = ?f j"
then obtain i j where i: "i \<le> Suc n" and j: "j < i"
and f: "?f i = ?f j" by rules
from j have i_nz: "Suc 0 \<le> i" by simp
from i have iSSn: "i \<le> Suc (Suc n)" by simp
have S0SSn: "Suc 0 \<le> Suc (Suc n)" by simp
show False
proof cases
assume fi: "f i = Suc n"
show False
proof cases
assume fj: "f j = Suc n"
from i_nz and iSSn and j have "f i \<noteq> f j" by (rule 0)
moreover from fi have "f i = f j"
ultimately show ?thesis ..
next
from i and j have "j < Suc (Suc n)" by simp
with S0SSn and le_refl have "f (Suc (Suc n)) \<noteq> f j"
by (rule 0)
moreover assume "f j \<noteq> Suc n"
with fi and f have "f (Suc (Suc n)) = f j" by simp
ultimately show False ..
qed
next
assume fi: "f i \<noteq> Suc n"
show False
proof cases
from i have "i < Suc (Suc n)" by simp
with S0SSn and le_refl have "f (Suc (Suc n)) \<noteq> f i"
by (rule 0)
moreover assume "f j = Suc n"
with fi and f have "f (Suc (Suc n)) = f i" by simp
ultimately show False ..
next
from i_nz and iSSn and j
have "f i \<noteq> f j" by (rule 0)
moreover assume "f j \<noteq> Suc n"
with fi and f have "f i = f j" by simp
ultimately show False ..
qed
qed
qed
moreover have "\<And>i. i \<le> Suc n \<Longrightarrow> ?f i \<le> n"
proof -
fix i assume "i \<le> Suc n"
hence i: "i < Suc (Suc n)" by simp
have "f (Suc (Suc n)) \<noteq> f i"
by (rule 0) (simp_all add: i)
moreover have "f (Suc (Suc n)) \<le> Suc n"
by (rule Suc) simp
moreover from i have "i \<le> Suc (Suc n)" by simp
hence "f i \<le> Suc n" by (rule Suc)
ultimately show "?thesis i"
by simp
qed
hence "\<exists>i j. i \<le> Suc n \<and> j < i \<and> ?f i = ?f j"
by (rule Suc)
ultimately show ?case ..
next
case (Suc k)
from search show ?case
proof
assume "\<exists>j<Suc k. f (Suc k) = f j"
thus ?case by (rules intro: le_refl)
next
assume nex: "\<not> (\<exists>j<Suc k. f (Suc k) = f j)"
have "\<exists>i j. i \<le> k \<and> j < i \<and> f i = f j"
proof (rule Suc)
from Suc show "k \<le> Suc (Suc n)" by simp
fix i j assume k: "Suc k \<le> i" and i: "i \<le> Suc (Suc n)"
and j: "j < i"
show "f i \<noteq> f j"
proof cases
assume eq: "i = Suc k"
show ?thesis
proof
assume "f i = f j"
hence "f (Suc k) = f j" by (simp add: eq)
with nex and j and eq show False by rules
qed
next
assume "i \<noteq> Suc k"
with k have "Suc (Suc k) \<le> i" by simp
thus ?thesis using i and j by (rule Suc)
qed
qed
thus ?thesis by (rules intro: le_SucI)
qed
qed
}
note r = this
show ?case by (rule r) simp_all
qed

text {*
The following proof, although quite elegant from a mathematical point of view,
*}

theorem pigeonhole_slow:
"\<And>f. (\<And>i. i \<le> Suc n \<Longrightarrow> f i \<le> n) \<Longrightarrow> \<exists>i j. i \<le> Suc n \<and> j < i \<and> f i = f j"
proof (induct n)
case 0
have "Suc 0 \<le> Suc 0" ..
moreover have "0 < Suc 0" ..
moreover from 0 have "f (Suc 0) = f 0" by simp
ultimately show ?case by rules
next
case (Suc n)
from search show ?case
proof
assume "\<exists>j < Suc (Suc n). f (Suc (Suc n)) = f j"
thus ?case by (rules intro: le_refl)
next
assume "\<not> (\<exists>j < Suc (Suc n). f (Suc (Suc n)) = f j)"
hence nex: "\<forall>j < Suc (Suc n). f (Suc (Suc n)) \<noteq> f j" by rules
let ?f = "\<lambda>i. if f i = Suc n then f (Suc (Suc n)) else f i"
have "\<And>i. i \<le> Suc n \<Longrightarrow> ?f i \<le> n"
proof -
fix i assume i: "i \<le> Suc n"
show "?thesis i"
proof (cases "f i = Suc n")
case True
from i and nex have "f (Suc (Suc n)) \<noteq> f i" by simp
with True have "f (Suc (Suc n)) \<noteq> Suc n" by simp
moreover from Suc have "f (Suc (Suc n)) \<le> Suc n" by simp
ultimately have "f (Suc (Suc n)) \<le> n" by simp
with True show ?thesis by simp
next
case False
from Suc and i have "f i \<le> Suc n" by simp
with False show ?thesis by simp
qed
qed
hence "\<exists>i j. i \<le> Suc n \<and> j < i \<and> ?f i = ?f j" by (rule Suc)
then obtain i j where i: "i \<le> Suc n" and ji: "j < i" and f: "?f i = ?f j"
by rules
have "f i = f j"
proof (cases "f i = Suc n")
case True
show ?thesis
proof (cases "f j = Suc n")
assume "f j = Suc n"
with True show ?thesis by simp
next
assume "f j \<noteq> Suc n"
moreover from i ji nex have "f (Suc (Suc n)) \<noteq> f j" by simp
ultimately show ?thesis using True f by simp
qed
next
case False
show ?thesis
proof (cases "f j = Suc n")
assume "f j = Suc n"
moreover from i nex have "f (Suc (Suc n)) \<noteq> f i" by simp
ultimately show ?thesis using False f by simp
next
assume "f j \<noteq> Suc n"
with False f show ?thesis by simp
qed
qed
moreover from i have "i \<le> Suc (Suc n)" by simp
ultimately show ?thesis using ji by rules
qed
qed

extract pigeonhole pigeonhole_slow

text {*
The programs extracted from the above proofs look as follows:
@{thm [display] pigeonhole_def}
@{thm [display] pigeonhole_slow_def}
The program for searching for an element in an array is
@{thm [display,eta_contract=false] search_def}
The correctness statement for @{term "pigeonhole"} is
@{thm [display] pigeonhole_correctness [no_vars]}

In order to analyze the speed of the above programs,
we generate ML code from them.
*}

consts_code
arbitrary :: "nat \<times> nat" ("{* (0::nat, 0::nat) *}")

generate_code
test = "\<lambda>n. pigeonhole n (\<lambda>m. m - 1)"
test' = "\<lambda>n. pigeonhole_slow n (\<lambda>m. m - 1)"
sel = "op !"

ML "timeit (fn () => test 10)"
ML "timeit (fn () => test' 10)"
ML "timeit (fn () => test 20)"
ML "timeit (fn () => test' 20)"
ML "timeit (fn () => test 25)"
ML "timeit (fn () => test' 25)"
ML "timeit (fn () => test 500)"

ML "pigeonhole 8 (sel [0,1,2,3,4,5,6,3,7,8])"

end
```